An experimental field test of female defense in territorial male collared lizards. (1st February 2023) - Baird, Troy A; Leibold, Dalton C
Abstract: A widely held principle in behavioral ecological research is that polygynous social systems evolve either by direct male defense of females or male defense of resources, although which of these mechanisms applies in particular species is rarely examined experimentally. We tested the relative importance of female versus resource defense in polygynous territorial male collared lizards ( Crotaphytus collaris ). Using a novel experimental design, we temporarily removed some of the resident females from male territories to create a female-free removal zone, whereas resident females were left intact within a non-removal zone. We then compared activity of males within each zone during three experimental phases; before we removed females, for two days when females were absent, and the day after return of females. If males defend females directly, we expected them to adjust the location of their patrol and display within removal and non-removal zones depending on the presence/absence of females, whereas we expected no such change if males defend resources. Male activity in the removal zone generally decreased when females were removed but then increased when females were replaced, whereas we observed the opposite pattern in the non-removal zone. The observed shifts in the location of patrol and display in response to the presence/absence of females, while resources remained constant, indicate that polygynous male collared lizards defend females directly. Our results suggest that male collared lizards take advantage of strong female philopatry to relatively small areas by focusing their patrol and display activities where potential mates reside. Abstract : Males may mate with multiple females either by defending them directly or by defending resources. However, tests to distinguish between these are rare. Collared lizard males decreased patrol and signaling in parts of their territories from which we had removed females and increased activity where other females remained. Increased tongue-flicking when females were present suggested that males may use chemical cues to search for mates. Our results indicate direct female defense in male collared lizards.